Regional Strain Determination and Myocardial Infarction Detection by Three‐Dimensional Echocardiography with Varied Temporal Resolution. Issue 2 (12th May 2014) - Zhu, Meihua; Streiff, Cole; Panosian, Jill; Zhang, Zhijun; Song, Xubo; Sahn, David J.; Ashraf, Muhammad
<x xml:space="preserve">Abstract</x> Background Three‐dimensional echocardiography (3DE) is a promising method for strain determination; however, there are temporal resolution concerns. This study aims to evaluate the feasibility and accuracy of 3DE on longitudinal and circumferential strain (LS, CS) determination and infarction detection under variable frame rates (FR) and "heart rates" (stroke rates [SR]) conditions. Methods Latex balloons were sewn into the left ventricle (LV) of 20 freshly harvested pig hearts which were then passively driven by a pulsatile pump apparatus at stroke volumes (SV) 30–70 mL. The hearts were pumped at 2 normal limits of human heart rate. Full‐volume data were acquired before and after a simulated myocardial infarction (MI) at the 2 most commonly used FRs. LS and CS values were evaluated against sonomicrometry. Results Longitudinal strain and CS derived from high FR acquisitions showed statistically superior correlations with sonomicrometry data (LS: R2 = 0.85, CS: R2 = 0.84) than strain values from low FR (LS: R2 = 0.78, CS: R2 = 0.76) (all P < 0.01). After MI induction, LS and CS at different FRs were significantly decreased while maintaining excellent correlations with sonomicrometry data (all P < 0.001). There is no statistical difference of strain values between different SR acquisitions. Conclusion Three‐dimensional wall‐motion tracking has the ability to accurately determine regional myocardial deformation and detect MI. Different heart rates within a physiologically relevant range have no effect on 3D strain accuracy. Strain values calculated from higher frame rate acquisitions were found to have a slightly better accuracy.